Comparative Transcriptome Analysis of the Expression of Antioxidant and Immunity Genes in the Spleen of a Cyanidin 3-O-Glucoside-Treated Alzheimer's Mouse Model - Varun Jaiswal; Miey Park; Hae-Jeung Lee (MDPI AG, 2021)
Cyanidin 3-O-glucoside (C3G) is a well-known antioxidant found as a dietary anthocyanin in different fruits and vegetables. It has protective and therapeutic effects on various diseases. It can reduce neuronal death from amyloid-beta (Aβ)-induced toxicity and promote the inhibition of Aβ fibrillization. Antioxidant and immune modulation might play a critical role in the properties of C3G against Alzheimer's disease (AD) and other diseases. However, limited studies have been performed on the mechanism involved in the effect of C3G through transcriptome analysis. Thus, the objective of this study was to perform comparative transcriptome analysis of the spleen to determine gene expression profiles of wild-type mice (C57BL/6J Jms), an Alzheimer's mouse model (APPswe/PS1dE9 mice), and a C3G-treated Alzheimer's mouse model. Differentially expressed antioxidant, immune-related, and AD pathways genes were identified in the treated group. The validation of gene expression data via RT-PCR studies further supported the current findings. Six important antioxidant genes (S100a8, S100a9, Prdx2, Hp, Mpst, and Prxl2a) and a high number of immune-related genes were found to be upregulated in the treatment groups, suggesting the possible antioxidant and immunomodulatory mechanisms of C3G, respectively. Further studies are strongly recommended to elucidate the precise role of these essential genes and optimize the therapeutic function of C3G in AD and other disease conditions.